Caspofungin Combined With TMP/SMZ in Treatment of Intractable Acute Pneumocystis jirovecii Pneumonia in Renal Transplant Recipients: Case Report and Literature Review - Hu, Hongtao; Xu, Shen; Jiang, Wen; Xu, Baoping; Wang, Jing; Xu, Gang (Clinical case reports, 2025)
ABSTRACT Pneumocystis jirovecii pneumonia (PJP) is a potential life‐threatening opportunistic infection that predominantly affects immunocompromised individuals, such as those with human immunodeficiency virus or organ transplant recipients. The treatment of PJP, particularly severe cases, remains challenging, as standardized treatment therapies often require prolonged durations without achieving significant clinical improvement. The present study describes the case of a 48‐year‐old female patient who suffered from severe refractory PJP following renal transplantation. Despite 3 weeks of conventional treatment, computed tomography images revealed persistent lung infection, and the PJP nucleic acid test remained positive. However, after initiating combination therapy with caspofungin and trimethoprim/sulfamethoxazole (TMP/SMZ) for 48 days, the PJP nucleic acid test yielded negative results, and marked resolution was observed in lung imaging. On the whole, in the management of PJP, particularly that of severe refractory cases following organ transplantation, extending the treatment duration may lead to improved outcomes. The case described herein demonstrates the potential efficacy of prolonged treatment with a combination of caspofungin and TMP/SMZ in facilitating infection clearance and promoting clinical recovery in non‐HIV patients with PJP.